Clinical and experimental evidences for a role of ABC transporters in the mechanisms underlying multidrug resistance in epilepsy - Lazarowski, Alberto (2006)
Epilepsy is a common neurological disorder affecting 1-2% of the general population. Although antiepileptic therapies efficiently control seizures in most patients, it is estimated that 20-25% of the affected population fails to achieve good control with antiepileptic drug (AED) treatment, thus defining refractory epilepsy (RE). Although the underlying mechanisms involved in AED resistance are poorly understood, it has been suggested that unresponsiveness to AEDs resembles the mechanism of resistance to chemotherapy in cancer. Considerable progress has bee attained recently in elucidating the molecular mechanisms of refractoriness during cancer chemotherapy. The foundational finding was that tumor cells become refractory to chemotherapeutic agents due to the action of the P-glycoprotein (P-gp), the product of the MDR-1 gene. P-gp acts as energy-dependent pumps that extrudes potentially toxic compounds out of the cells and can confer resistance levels of 1000-fold or more to the expressing cells.